A polylactic acid heat-resistant 3D printing wire and a preparation method thereof
Patent Information
- Application Number
- CN202611139000.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-29
- Publication Date
- 2026-10-27
AI Technical Summary
[0009]本发明提供一种聚乳酸耐热型3D打印线材及其制备方法,可以解决现有技术中PLA基3D打印线材耐热性能不足,且现有改性手段难以兼顾耐热性与韧性的问题
1、本发明通过聚乳酸(PLA)、聚丁二酸丁二醇酯(PBS)和立构复合聚乳酸(sc-PLA)三元基体复配,结合精氨酸聚酯酰胺增韧剂和改性纳米纤维素增强填料,在sc-PLA形成的高熔点立构复合晶体、增韧剂中呋喃杂环的刚性结构、改性纳米纤维素表面SiO2无机层及交联网络中苯环刚性基团的共同作用下,显著提升了线材的耐热性能。
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] This invention relates to the field of printing materials technology, and in particular to a polylactic acid heat-resistant 3D printing filament and its preparation method. Background Technology
[0002] Polylactic acid (PLA) is a bio-based biodegradable polymer material made from renewable plant resources. Due to its good melt processing, printability, and biocompatibility, it has become one of the most widely used filament matrix materials in the field of fused deposition modeling (FDM) 3D printing.
[0003] However, PLA's poor heat resistance is one of the main bottlenecks in its application in 3D printing. PLA's glass transition temperature (Tg) is only 55–65°C, and its products begin to soften and deform when the temperature exceeds 60°C, resulting in a significant decrease in mechanical properties. This deficiency severely limits the application of PLA-based 3D printing filaments in high-temperature environments, such as automotive parts, electronic appliance housings, and outdoor structural components—scenarios where high heat resistance is required.
[0004] To improve the heat resistance of PLA, the following solutions are commonly used in existing technologies: (1) Adding inorganic nucleating agents: By introducing nucleating agents such as talc and montmorillonite, PLA crystallization is promoted, and its crystallinity is improved to enhance its heat resistance. However, this method has a limited effect on improving heat resistance, and excessive addition of inorganic fillers will lead to a significant decrease in wire toughness, making the printed product brittle and prone to cracking.
[0005] (2) Blending with high heat-resistant polymers: PLA is blended with heat-resistant polymers such as polycarbonate (PC) and acrylonitrile-butadiene-styrene copolymer (ABS). However, such blends often have poor compatibility and weak interfacial bonding. The overall mechanical properties of the blends are often inferior to those of the single components, and the introduction of non-biodegradable components destroys the fully biodegradable properties of PLA.
[0006] (3) Post-annealing crystallization treatment: The crystallinity of PLA products is improved by hot annealing. Although this method can improve the heat resistance to a certain extent, the processing cycle is long and the energy consumption is high. Moreover, for 3D printed products, annealing can easily lead to warping and deformation and a decrease in dimensional accuracy.
[0007] (4) Addition of stereocomposite polylactic acid (sc-PLA): Stereocomposite crystals are formed using L-polylactic acid (PLLA) and D-polylactic acid (PDLA), with a melting point of up to 230℃, which is much higher than that of homogeneous crystallization of pure PLA. The introduction of sc-PLA can effectively improve the crystallization rate and crystallinity of the PLA matrix, thereby improving heat resistance. However, sc-PLA itself is relatively brittle, and high addition amounts can lead to a sharp decrease in material toughness, making it difficult to meet the requirements of 3D printing filaments for flexibility and impact resistance.
[0008] In summary, existing solutions for improving the heat resistance of PLA-based 3D printing filaments are all insufficient to simultaneously enhance heat resistance while maintaining material toughness, processability, and biodegradability. There is an urgent need to develop a PLA-based filament that combines excellent heat resistance, high toughness, and good 3D printing adaptability. Summary of the Invention
[0009] This invention provides a heat-resistant polylactic acid (PLA) 3D printing filament and its preparation method, which can solve the problems of insufficient heat resistance of PLA-based 3D printing filaments in the prior art, and the difficulty of existing modification methods in achieving both heat resistance and toughness.
[0010] The objective of this invention can be achieved through the following technical solutions: In a first aspect, the present invention provides a polylactic acid heat-resistant 3D printing filament, comprising the following raw materials in parts by weight: Polylactic acid (PLA) 50-80 parts; polybutylene succinate (PBS) 10-30 parts; stereopolymer polylactic acid (sc-PLA) 5-20 parts; toughening agent 2-10 parts; modified nanocellulose 1-5 parts; antioxidant 0.1-1 part; lubricant 0.2-1.5 parts; The toughening agent is arginine polyester amide; The modified nanocellulose is a cross-linked nanocellulose with a surface coated with silica and modified with an epoxy silane coupling agent containing hydrophobic long chains. The cross-linked nanocellulose is formed by cross-linking polyethyleneimine with glutaraldehyde and 4,4'-dithiodibenzaldehyde.
[0011] This invention significantly improves the heat resistance of wires by combining a ternary matrix of polylactic acid (PLA), polybutylene succinate (PBS), and stereocomposite polylactic acid (sc-PLA), along with arginine polyesteramide toughening agent and modified nanocellulose reinforcing filler. This is achieved through the combined effects of the high-melting-point stereocomposite crystals induced by the stereocomposite polylactic acid, the rigid structure of the furan heterocycles in the toughening agent, and the conjugated benzene rings in the silica inorganic layer and cross-linked network on the surface of the modified nanocellulose. Furthermore, the flexible long-chain segments in the arginine polyesteramide molecular chain synergistically toughen the wires through the long-chain epoxy silane coupling agent grafted onto the surface of the modified nanocellulose. During melt blending, the epoxy groups on the surface of the modified nanocellulose can undergo ring-opening reactions with the amino groups on the arginine polyesteramide toughening agent molecular chain to form chemical bonds. It can also react with the terminal carboxyl and hydroxyl groups of PLA and PBS, significantly improving the compatibility of the inorganic-organic interface and the compatibility between matrices. This effectively transfers and disperses stress while enhancing toughness, giving the filament both good tensile strength and elongation at break, achieving a synergistic improvement in heat resistance and mechanical properties. Furthermore, the guanidine groups on the arginine polyesteramide molecular chain and the polyethyleneimine in the modified nanocellulose crosslinking layer together endow the filament with excellent antibacterial properties. The dynamic covalent bond characteristics of disulfide bonds (-SS-) and imine bonds (-C=N-) in the crosslinking network endow the material with intrinsic self-healing properties, enabling the printed parts to repair microcracks during use and extend their service life. Ultimately, a multifunctional polylactic acid-based 3D printing filament with excellent heat resistance, mechanical properties, antibacterial properties, and self-healing properties is obtained.
[0012] Furthermore, the polylactic acid is L-polylactic acid (PLLA) with a melt index (190℃ / 2.16kg) of 5–15 g / 10 min. This melt index range ensures that PLLA has a suitable molecular weight, guaranteeing good flowability during melt blending and 3D printing, while also ensuring sufficient mechanical strength after filament molding. This avoids embrittlement of the product due to an excessively high melt index (too low molecular weight) or processing difficulties due to an excessively low melt index.
[0013] Furthermore, the polybutylene succinate has a number-average molecular weight of 80,000–120,000 and a melting point of 110–120°C. This molecular weight range endows PBS with good mechanical properties and melt strength, forming a suitable melting temperature match with the PLA matrix, ensuring that the two can be fully melt-mixed at the blending processing temperature, while exerting an effective toughening and modification effect.
[0014] Furthermore, the stereocomposite polylactic acid is composed of L-polylactic acid and D-polylactic acid in a 1:1 mass ratio. This mass ratio maximizes the formation efficiency of the stereocomposite crystals, constructing a high-melting-point three-dimensional stereocomposite network structure in the matrix, thereby most effectively improving the heat resistance of the wire.
[0015] Furthermore, the toughening agent is prepared by: A1. Triethylamine and p-nitrophenol were added to acetone, and the reaction was kept at 0°C using an ice bath to obtain a cooling solution. 2,5-furandicarboxylic acid chloride was diluted in cold acetone and then added to the cooling solution. The mixture was stirred at 0°C for 2-3 hours and left overnight at room temperature. The precipitate was washed, recrystallized, and dried under vacuum to constant weight to obtain monomer 1. In the above steps, 2,5-furandicarboxylic acid chloride and p-nitrophenol undergo a nucleophilic acyl substitution reaction at low temperature (0°C) via triethylamine bound acid to prepare a bis-p-nitrophenol active ester monomer (monomer 1) containing a furan heterocycle. The rigid structure of the furan heterocycle helps to improve the heat resistance of the toughening agent and the final wire, while the active ester group provides high reactivity for the subsequent polycondensation reaction.
[0016] A2. L-arginine and 1,6-hexanediol were directly mixed, followed by the addition of toluene and p-toluenesulfonic acid monohydrate. The mixture was heated to 130°C and stirred under reflux for 24 hours. After cooling to room temperature, the toluene precipitated and was poured off. The product was then dissolved in isopropanol at 75°C under stirring, and then precipitated at 4°C. This process was repeated 3 times to obtain monomer 2. In the above steps, under acid catalysis, the carboxyl group of L-arginine undergoes a Fischer esterification reaction with the hydroxyl group of 1,6-hexanediol. At the same time, the guanidinyl group and α-amino group of the arginine side chain are protected as protonated salts in an acidic environment and do not participate in side reactions, thus obtaining an arginine-hexanediol ester monomer (monomer 2) with a primary amino group at the end. The flexible long chain segment provided by 1,6-hexanediol endows the toughening agent with good flexibility and toughening effect, while the guanidinyl group is completely retained to endow it with antibacterial properties.
[0017] A3. Add monomer 1 and monomer 2 to anhydrous DMSO, stir and dissolve at 120°C, add triethylamine, stop stirring, keep at 80°C overnight, add the mixed solution dropwise to pre-cooled ethyl acetate to precipitate, stir, wash, and dry to constant weight to obtain toughening agent.
[0018] In the above steps, under alkaline conditions, the p-nitrophenol active ester group of monomer 1 undergoes a nucleophilic substitution reaction with the primary amino group of monomer 2 to form an amide bond. Through stepwise polycondensation, an arginine polyesteramide toughening agent containing alternating furan rings, arginine guanidine groups, and flexible hexanediol segments is obtained. This structure enables the toughening agent to have both rigid heat-resistant segments and flexible toughening segments. At the same time, the guanidine group imparts intrinsic antibacterial properties, while the amino group can react with the epoxy groups of modified nanocellulose to form chemical bonds during the subsequent melt blending process, significantly improving interfacial compatibility.
[0019] Further, in step A1, the ratio of triethylamine, p-nitrophenol, and acetone in the cooling liquid is 32.4g:43.1g:200mL. This ratio ensures that triethylamine and p-nitrophenol are equimolar, ensuring that p-nitrophenol is fully deprotonated to promote the nucleophilic substitution reaction. The ratio of 2,5-furandicarboxylic chloride, cold acetone, and cooling liquid is 30g:100mL:200mL. 2,5-furandicarboxylic chloride reacts with p-nitrophenol in the required stoichiometric ratio, so that the diacyl chloride is fully converted into diester, reducing byproducts.
[0020] Further, in step A2, the ratio of L-arginine, 1,6-hexanediol, toluene, and p-toluenesulfonic acid monohydrate is 7g:2.4g:400mL:15.6g. This ratio ensures that the arginine carboxyl group is fully esterified with excess hexanediol, and the large amount of toluene acts as a dehydrating solvent to continuously remove the generated water, driving the esterification equilibrium to the right and increasing the yield of monomer 2.
[0021] Furthermore, in step A3, the ratio of monomer 1, monomer 2, anhydrous DMSO, and triethylamine is 0.73g:0.86g:3mL:5mL. This ratio ensures that monomer 1 and monomer 2 are added in equal molar amounts, which is beneficial for obtaining a toughening agent with a higher degree of polymerization in the polycondensation reaction.
[0022] Nanocellulose possesses a high specific surface area and excellent mechanical strength, and as a filler, it can significantly improve the mechanical properties and heat resistance of polylactic acid (PLA) matrices. However, the surface of nanocellulose is rich in polar hydroxyl groups, resulting in poor interfacial compatibility with hydrophobic PLA matrices, easy aggregation, and insufficient thermal stability. Direct addition of nanocellulose is difficult to achieve the desired reinforcing effect and may even lead to material performance degradation. Therefore, the present invention makes the following improvements.
[0023] Furthermore, the method for preparing the modified nanocellulose is as follows: S1. Add polyethyleneimine to the nanocellulose dispersion, stir for 5-10 min, add glutaraldehyde aqueous solution and 4,4'-dithiodimethylbenzaldehyde solution, stir at 40-50℃ for 3-5 h, centrifuge, wash, and dry to obtain cross-linked nanocellulose; In the above steps, the abundant amino groups on the polyethyleneimine (PEI) molecular chain react with the aldehyde groups at both ends of glutaraldehyde and 4,4'-dithiodibenzaldehyde to form an organic cross-linked network on the surface of nanocellulose. PEI can electrostatically adsorb onto the negatively charged bacterial cell membrane, disrupting the cell membrane structure and leading to bacterial death, thus endowing the modified nanocellulose with intrinsic antibacterial activity. At the same time, the imine bonds (-C=N-) generated by the reaction and the disulfide bonds (-SS-) introduced by 4,4'-dithiodibenzaldehyde are both dynamic covalent bonds. Together, they endow the cross-linked network with reversible exchange capacity and intrinsic self-healing properties, enabling microcracks generated during the processing or use of modified nanocellulose to repair themselves under certain conditions. The rigid benzene ring groups in the 4,4'-dithiodibenzaldehyde molecular structure improve the rigidity and thermal stability of the cross-linked layer. In addition, the formation of the cross-linked network provides an ideal interfacial basis for the uniform deposition of the subsequent inorganic layer.
[0024] S2. Add cross-linked nanocellulose to an ethanol aqueous solution, then add tetraethyl orthosilicate, adjust the pH to 8, stir at 40-50℃ for 2-4 hours, centrifuge, wash, and dry to obtain SiO2@cross-linked nanocellulose; In the above steps, under weakly alkaline conditions, tetraethyl orthosilicate (TEOS) undergoes a hydrolysis-condensation sol-gel reaction in an aqueous ethanol solution, generating a nano-silica coating layer in situ on the surface of cross-linked nanocellulose. This inorganic layer not only improves the thermal stability of nanocellulose, but also provides abundant silanol active anchor sites for subsequent coupling agent modification, which is beneficial for the uniform bonding of coupling agent molecules on its surface.
[0025] S3. Add SiO2@crosslinked nanocellulose to an ethanol aqueous solution, add 8-glycidoxyoctyltrimethoxysilane, stir and react at 50-60℃ for 2-4 hours, centrifuge, wash, and dry to obtain modified nanocellulose.
[0026] In the above steps, the silanol groups generated after the hydrolysis of the methoxysilane end of the 8-glycidoxyoctyltrimethoxysilane molecule undergo a condensation reaction with the silanol groups on the surface of SiO2@crosslinked nanocellulose, thus covalently grafting them onto the surface of nanocellulose. The long-chain octyl hydrophobic segments can significantly improve the dispersion compatibility of nanocellulose in the PLA matrix. On the other hand, their flexible long chains act as toughening spacers, dissipating impact energy through chain segment movement under external force, thus endowing the modified nanocellulose with its own toughening function. During the melt blending process, the terminal epoxy groups can undergo ring-opening reactions with the terminal carboxyl groups and hydroxyl groups of PLA / PBS, as well as the amino groups of the arginine polyester amide toughening agent, to form chemical bonds, thereby enhancing the interfacial bonding force and achieving a synergistic effect of reinforcement and toughening.
[0027] Further, in step S1, the ratio of the aqueous dispersion of nanocellulose, polyethyleneimine, glutaraldehyde aqueous solution, and 4,4'-dithiodibenzaldehyde solution is 100 mL : 0.75–1.25 g : 0.6–1.2 mL : 2–6 mL; this ratio ensures the formation of a polyethyleneimine cross-linked layer with a moderate cross-linking density and a dynamic disulfide bond network on the surface of the nanocellulose. The ratio of nanocellulose to deionized water in the nanocellulose dispersion is 1 g : 100 mL; this solid content ensures uniform dispersion of the nanocellulose, facilitating subsequent cross-linking reactions.
[0028] The glutaraldehyde aqueous solution has a mass fraction of 25 wt%; this concentration allows glutaraldehyde to efficiently form Schiff base crosslinking bonds with the amino groups of polyethyleneimine. The ratio of 4,4'-dithiodiphenylbenzaldehyde to anhydrous ethanol in the 4,4'-dithiodiphenylbenzaldehyde solution is 1 g: 15-25 mL, preferably 1 g: 20 mL. This concentration ensures that 4,4'-dithiodiphenylbenzaldehyde is fully dissolved and participates uniformly in the crosslinking reaction, introducing dynamic disulfide bonds.
[0029] Further, in step S2, the ratio of the cross-linked nanocellulose, the ethanol aqueous solution, and the tetraethyl orthosilicate is 1g:50-80mL:2-5mL; the volume ratio of anhydrous ethanol to deionized water in the ethanol aqueous solution is 4:1. This ratio allows the tetraethyl orthosilicate to undergo uniform hydrolysis and condensation on the surface of the cross-linked nanocellulose under alkaline conditions to form a silica coating layer, thereby improving thermal stability and rigidity.
[0030] Further, in step S3, the ratio of SiO2@crosslinked nanocellulose, ethanol aqueous solution, and 8-glycidoxyoctyltrimethoxysilane is 1g:60-80mL:0.2-0.4g; the volume ratio of anhydrous ethanol to deionized water in the ethanol aqueous solution is 4:1. This ratio ensures that 8-glycidoxyoctyltrimethoxysilane forms effective grafts on the surface of SiO2@crosslinked nanocellulose. If the amount is too low, the grafting amount will be insufficient and the reinforcing effect will be insignificant; if the amount is too high, self-condensation side reactions will easily occur between coupling agent molecules, resulting in waste of raw materials and being detrimental to the modification effect.
[0031] Furthermore, the antioxidant is vitamin E and / or rosemary extract. Naturally derived antioxidants effectively inhibit the thermal oxidative degradation of polylactic acid during processing, while maintaining the material's bio-based properties and biocompatibility.
[0032] Furthermore, the lubricant is carnauba wax and / or bio-based stearate. Bio-based lubricants reduce friction between the melt and processing equipment, improve extrusion molding properties and wire surface finish, and have good compatibility with polylactic acid systems. Secondly, the present invention provides a method for preparing polylactic acid heat-resistant 3D printing filament, comprising the following steps: (1) Weigh polylactic acid, polybutylene succinate, stereocomposite polylactic acid, toughening agent, modified nanocellulose, antioxidant and lubricant according to the weight parts, add them to a high-speed mixer to obtain a premix; this step makes the components uniformly dispersed, providing a uniform raw material basis for subsequent melt blending.
[0033] (2) Add the premix to a twin-screw extruder and perform melt blending extrusion to obtain a melt blend. Utilize the high shear mixing effect of the twin-screw extruder to fully combine PLA, PBS, sc-PLA, toughening agent and modified nanocellulose in the molten state, thereby promoting the interfacial reaction and compatibility improvement between the components.
[0034] (3) The melt blend is cooled by water and granulated to obtain granules; this step allows the melt blend to cool and solidify quickly, which is convenient for subsequent single-screw extrusion molding.
[0035] (4) The granules are dried and then fed into a single-screw extruder. After melting, extrusion, cooling, traction, and winding, a 3D printing filament with a diameter of 1.75±0.05mm is obtained. This step allows the granules to be remelted and stably extruded through a single screw to obtain a 3D printing filament with precise dimensions and a smooth surface.
[0036] Furthermore, in step (1), the specific parameters of the high-speed mixer are: mixing at a speed of 300-500 rpm for 5-15 minutes. This speed and time range ensures that each component is efficiently mixed while avoiding excessive shearing that could lead to resin molecular chain breakage or local overheating, thus obtaining a premix with uniform component distribution.
[0037] Further, in step (2), the specific parameters of the twin-screw extruder are as follows: the extruder temperature is set to 150-170℃ in zone 1, 170-190℃ in zone 2, 190-210℃ in zone 3, and 200-220℃ in zone 4; the die head temperature is 210-225℃; and the screw speed is 200-300 rpm. This stepped heating and screw speed setting ensures that each component gradually melts and is fully mixed at a suitable temperature, which not only ensures complete melting of sc-PLA and sufficient interfacial reaction, but also avoids excessively high processing temperatures that could lead to thermal degradation of PLA.
[0038] Further, in step (4), the specific parameters of the single-screw extruder are as follows: the temperature of the single-screw extruder is 170-190℃ in zone one, 190-210℃ in zone two, 200-220℃ in zone three, the die head temperature is 210-230℃, and the screw speed is 30-60 rpm. This temperature and speed setting ensures that the filament has good fluidity and extrusion stability during the melt extrusion process, resulting in 3D printed filaments with uniform diameter and smooth surface.
[0039] Furthermore, in step (4), the temperature of the cooling water tank is 20-40°C. This water temperature ensures that the extruded wire is cooled and shaped evenly during the traction process, avoiding excessive internal stress or uneven shrinkage due to sudden cooling, and ensuring the accuracy of wire diameter and roundness.
[0040] The beneficial effects of this invention are: 1. This invention significantly improves the heat resistance of wire by combining a ternary matrix of polylactic acid (PLA), polybutylene succinate (PBS), and stereocomposite polylactic acid (sc-PLA), along with arginine polyesteramide toughening agent and modified nanocellulose reinforcing filler. Under the combined effect of the high melting point stereocomposite crystals formed by sc-PLA, the rigid structure of furan heterocycles in the toughening agent, the SiO2 inorganic layer on the surface of modified nanocellulose, and the rigid benzene ring groups in the crosslinking network.
[0041] 2. This invention utilizes the synergistic toughening effect of flexible long-chain segments in the arginine polyester amide molecular chain and long-chain epoxy silane coupling agents grafted onto the surface of modified nanocellulose. During the melt blending process, the epoxy groups undergo ring-opening reactions with the PLA / PBS end groups and the toughening agent amino groups to form chemical bonds, which significantly improves interfacial compatibility and stress transfer efficiency, enabling the wire to have both good tensile strength and elongation at break, and achieving a synergistic improvement in heat resistance and mechanical properties.
[0042] 3. In this invention, the guanidine group on the arginine polyester amide molecular chain and the polyethyleneimine in the modified nanocellulose crosslinking layer together endow the wire with excellent antibacterial properties.
[0043] 4. In this invention, the disulfide bonds (-SS-) and imine bonds (-C=N-) in the modified nanocellulose crosslinking network are both dynamic covalent bonds, which endow the material with intrinsic self-healing properties, enabling the printed parts to repair microcracks during use and extend their service life.
[0044] 5. This invention uses vitamin E and / or rosemary extract as natural antioxidants and carnauba wax and / or bio-based stearate as bio-based lubricants, which are highly compatible with the biodegradability of PLA / PBS, ensuring the green and environmentally friendly properties of the material system. Detailed Implementation
[0045] The specific embodiments of the present invention will be described in detail below, but it should be understood that the scope of protection of the present invention is not limited to the specific embodiments.
[0046] Preparation Example 1 The toughening agent in this preparation example is prepared as follows: A1. Add 32.4 g of triethylamine and 43.1 g of p-nitrophenol to 200 mL of acetone, and maintain the reaction at 0 °C using an ice bath to obtain a cooling solution. Dilute 30 g of 2,5-furandicarboxylic acid chloride in 100 mL of cold acetone, and then add it dropwise to 200 mL of the cooling solution. Stir at 0 °C for 2 h, and let it stand overnight at room temperature. Precipitate, wash, recrystallize, and vacuum dry to constant weight to obtain monomer 1. A2. 7g L-arginine and 2.4g 1,6-hexanediol were directly mixed, followed by the addition of 400mL toluene and 15.6g p-toluenesulfonic acid monohydrate. The mixture was heated to 130℃ and stirred under reflux for 24h. After cooling to room temperature, the toluene precipitated and was poured off. The product was then dissolved in isopropanol at 75℃ under stirring, and then precipitated at 4℃. This process was repeated 3 times to obtain monomer 2. A3. Add 0.73g of monomer 1 and 0.86g of monomer 2 to 3mL of anhydrous DMSO, stir and dissolve at 120℃, add 5mL of triethylamine, stop stirring, keep at 80℃ overnight, add the mixed solution dropwise to pre-cooled ethyl acetate to precipitate, stir, wash, and dry to constant weight to obtain toughening agent.
[0047] Preparation Example 2 The preparation method of modified nanocellulose in this preparation example is as follows: S1. Add 0.75 g of polyethyleneimine to 100 mL of nanocellulose dispersion (the ratio of nanocellulose to deionized water in the nanocellulose dispersion is 1 g: 100 mL), stir for 5 min, add 0.6 mL of 25 wt% glutaraldehyde aqueous solution and 2 mL of 4,4'-dithiodiphenylbenzaldehyde solution (the ratio of 4,4'-dithiodiphenylbenzaldehyde to anhydrous ethanol in the 4,4'-dithiodiphenylbenzaldehyde solution is 1 g: 20 mL), stir at 40 °C for 3 h, centrifuge, wash, and dry to obtain cross-linked nanocellulose; S2. Add 1g of cross-linked nanocellulose to 50mL of ethanol aqueous solution. The volume ratio of anhydrous ethanol to deionized water in the ethanol aqueous solution is 4:1. Then add 2mL of tetraethyl orthosilicate. Adjust the pH to 8 with 25wt% ammonia water. Stir at 40℃ for 2h, centrifuge, wash, and dry to obtain SiO2@cross-linked nanocellulose. S3. Add 1g of SiO2@crosslinked nanocellulose to 60mL of ethanol aqueous solution, where the volume ratio of anhydrous ethanol to deionized water in the ethanol aqueous solution is 4:1. Add 0.2g of 8-glycidoxyoctyltrimethoxysilane, stir and react at 50℃ for 2h, centrifuge, wash, and dry to obtain modified nanocellulose.
[0048] Preparation Example 3 The preparation method of modified nanocellulose in this preparation example is as follows: S1. Add 1g of polyethyleneimine to 100mL of nanocellulose dispersion (the ratio of nanocellulose to deionized water in the nanocellulose dispersion is 1g:100mL), stir for 8min, add 0.9mL of 25wt% glutaraldehyde aqueous solution and 4mL of 4,4'-dithiodiphenylbenzaldehyde solution (the ratio of 4,4'-dithiodiphenylbenzaldehyde to anhydrous ethanol in the 4,4'-dithiodiphenylbenzaldehyde solution is 1g:20mL), stir at 45℃ for 4h, centrifuge, wash, and dry to obtain cross-linked nanocellulose; S2. Add 1g of cross-linked nanocellulose to 65mL of ethanol aqueous solution, where the volume ratio of anhydrous ethanol to deionized water in the ethanol aqueous solution is 4:1. Then add 3.5mL of tetraethyl orthosilicate, adjust the pH to 8 with 25wt% ammonia water, stir at 45℃ for 3h, centrifuge, wash, and dry to obtain SiO2@cross-linked nanocellulose. S3. Add 1g of SiO2@crosslinked nanocellulose to 70mL of ethanol aqueous solution, where the volume ratio of anhydrous ethanol to deionized water in the ethanol aqueous solution is 4:1. Add 0.3g of 8-glycidoxyoctyltrimethoxysilane, stir and react at 55℃ for 3h, centrifuge, wash, and dry to obtain modified nanocellulose.
[0049] Preparation Example 4 The preparation method of modified nanocellulose in this preparation example is as follows: S1. Add 1.25 g of polyethyleneimine to 100 mL of nanocellulose dispersion (the ratio of nanocellulose to deionized water in the nanocellulose dispersion is 1 g: 100 mL), stir for 10 min, add 1.2 mL of 25 wt% glutaraldehyde aqueous solution and 6 mL of 4,4'-dithiodiphenylbenzaldehyde solution (the ratio of 4,4'-dithiodiphenylbenzaldehyde to anhydrous ethanol in the 4,4'-dithiodiphenylbenzaldehyde solution is 1 g: 20 mL), stir at 50 °C for 5 h, centrifuge, wash, and dry to obtain cross-linked nanocellulose; S2. Add 1g of cross-linked nanocellulose to 80mL of ethanol aqueous solution. The volume ratio of anhydrous ethanol to deionized water in the ethanol aqueous solution is 4:1. Then add 5mL of tetraethyl orthosilicate. Adjust the pH to 8 with 25wt% ammonia water. Stir at 50℃ for 4h, centrifuge, wash, and dry to obtain SiO2@cross-linked nanocellulose. S3. Add 1g of SiO2@crosslinked nanocellulose to 80mL of ethanol aqueous solution, where the volume ratio of anhydrous ethanol to deionized water in the ethanol aqueous solution is 4:1. Add 0.4g of 8-glycidoxyoctyltrimethoxysilane, stir and react at 60℃ for 4h, centrifuge, wash, and dry to obtain modified nanocellulose.
[0050] Compare with Example 1 The only difference between this comparative example and preparation example 2 is that, in step S3, "3-glycidoxypropyltrimethoxysilane" is used instead of "8-glycidoxyoctyltrimethoxysilane".
[0051] Compare with Example 2 The only difference between this comparative example and preparation example 2 is that step S3 is omitted, and SiO2@crosslinked nanocellulose is used as modified nanocellulose.
[0052] Compare with Example 3 The only difference between this comparative example and preparation example 2 is that steps S3 and S2 are omitted, and cross-linked nanocellulose is used as modified nanocellulose.
[0053] Compare with Example 4 The only difference between this comparative example and preparation example 2 is that steps S3 and S2, as well as 4,4'-dithiodimethylbenzaldehyde in step S1, are omitted. The specific steps are as follows: Add 0.75 g of polyethyleneimine to 100 mL of nanocellulose dispersion (the ratio of nanocellulose to deionized water in the nanocellulose dispersion is 1 g: 100 mL), stir for 5 min, add 0.6 mL of 25 wt% glutaraldehyde aqueous solution, stir at 40 °C for 3 h, centrifuge, wash, and dry to obtain modified nanocellulose.
[0054] Example 1 This embodiment provides a polylactic acid heat-resistant 3D printing filament, comprising the following parts by weight of raw materials: 50 parts of polylactic acid (PLA); 10 parts of polybutylene succinate (PBS); 5 parts of stereocomposite polylactic acid (sc-PLA); 2 parts of the toughening agent obtained in Preparation Example 1; 1 part of the modified nanocellulose obtained in Preparation Example 2; 0.1 parts of vitamin E; 0.2 parts of carnauba wax; Polybutylene succinate has a number-average molecular weight of 80,000 and a melting point of 110°C.
[0055] Among them, polylactic acid is L-polylactic acid (PLLA), and the melt index (190℃ / 2.16kg) is 15g / 10min; The stereocomposite polylactic acid is composed of L-polylactic acid and D-polylactic acid in a mass ratio of 1:1.
[0056] The preparation steps are as follows: (1) Weigh polylactic acid, polybutylene succinate, stereocomposite polylactic acid, toughening agent, modified nanocellulose, antioxidant and lubricant according to the weight parts, add them to a high-speed mixer, mix at 400 rpm for 10 min to obtain a premix; (2) Add the premixed material into the twin-screw extruder and perform melt blending extrusion to obtain a melt blend. The specific parameters of the twin-screw extruder are: the extruder temperature is set to 160℃ in zone 1, 180℃ in zone 2, 200℃ in zone 3, 210℃ in zone 4, the die head temperature is 220℃, and the screw speed is 250rpm. (3) The melt blend is cooled with water and pelletized to obtain granules; (4) The granules are dried and then added to a single screw extruder. The temperature of the single screw extruder is 180℃ in zone 1, 200℃ in zone 2, 210℃ in zone 3, 220℃ at the die head, and 50 rpm at the screw speed. After melting, extrusion, cooling, and cooling in a water bath at 30℃, the 3D printing filament with a diameter of 1.75±0.05mm is obtained by traction and winding.
[0057] Examples 2 and 3 describe a heat-resistant polylactic acid (PLA) 3D printing filament. The only difference between this example and Example 1 is the adjustment of the raw material ratio for the PLA heat-resistant 3D printing filament, as shown in Table 1. Table 1. Raw material list for Examples 1 to 3
[0058] Example 4 The only difference between this embodiment and Example 3 is that the modified nanocellulose obtained in Example 2 is replaced with an equal amount of the modified nanocellulose obtained in Example 3.
[0059] Example 5 The only difference between this embodiment and Example 3 is that the modified nanocellulose obtained in Example 2 is replaced with an equal amount of the modified nanocellulose obtained in Example 4.
[0060] Comparative Example 1 The only difference between this comparative example and Example 1 is that the modified nanocellulose obtained in Preparation Example 2 was replaced with an equal amount of the modified nanocellulose obtained in Control Example 1.
[0061] Comparative Example 2 The only difference between this comparative example and Example 1 is that the modified nanocellulose obtained in Preparation Example 2 was replaced with an equal amount of the modified nanocellulose obtained in Control Example 2.
[0062] Comparative Example 3 The only difference between this comparative example and Example 1 is that the modified nanocellulose obtained in Preparation Example 2 was replaced with an equal amount of the modified nanocellulose obtained in Control Example 3.
[0063] Comparative Example 4 The only difference between this comparative example and Example 1 is that the modified nanocellulose obtained in Preparation Example 2 was replaced with an equal amount of the modified nanocellulose obtained in Control Example 4.
[0064] Comparative Example 5 The only difference between this comparative example and Example 1 is that the modified nanocellulose obtained in Preparation Example 2 was replaced with an equal amount of nanocellulose.
[0065] Comparative Example 6 The only difference between this comparative example and Example 1 is that the toughening agent is omitted.
[0066] Comparative Example 7 The only difference between this comparative example and Example 1 is that the modified nanocellulose is omitted.
[0067] The performance of polylactic acid heat-resistant 3D printing filaments obtained in Examples 1 to 5 and Comparative Examples 1 to 7 was tested. The test items are as follows, and the test results are shown in Table 2: (1) Heat resistance test: The heat distortion temperature test was carried out in accordance with GB / T1634.2-2019. The sample was made into a standard specimen of 80mm×10mm×4mm, with a load of 1.80MPa and a heating rate of 120℃ / h. The heat distortion temperature HDT (℃) was recorded. (2) Mechanical property testing: Tensile strength and elongation at break were determined according to GB / T 1040.3-2006 standard; (3) Antibacterial performance test: According to GB / T 31402-2023 standard, the sample was injection molded into a smooth sample piece of 50mm×50mm×2mm, sterilized at 121°C and 0.1MPa for 20min, and then 0.2mL of 1×10 5 A CFU / mL suspension of Escherichia coli or Staphylococcus aureus was prepared and spread evenly. The suspension was statically cultured for 24 h at 37 °C and relative humidity ≥90%. Then, the suspension was eluted with 20 mL of sterile physiological saline and shaken for 10 min. The eluent was serially diluted and spread for counting. The antibacterial rate was calculated as (average colony count of blank sample - average colony count of sample) / average colony count of blank sample × 100%.
[0068] (4) Self-healing performance test: Use a scalpel to make an incision in the middle of the sample, with a depth of 1 mm. Close the incision tightly, press with your finger for 1 minute, and then put it in a 60°C oven for 12 hours to repair. Measure the tensile strength of the repaired sample according to the above mechanical property test method, and calculate the self-healing efficiency.
[0069] Table 2
[0070] Note: In Table 2, " / " indicates that this feature is basically not available.
[0071] As shown in Table 2, Examples 1-5 all exhibited excellent overall performance. With increasing amounts of toughening agent and modified nanocellulose in the formulation, Examples 2 and 3 showed progressively improved heat distortion temperature and mechanical properties compared to Example 1. Examples 4 and 5, compared to Example 3, benefited from the increased crosslinking density in the modified nanocellulose crosslinking layer, further enhancing the integrity of the crosslinking network and the dynamic bond density, resulting in progressively stronger thermal stability, mechanical properties, and self-healing efficiency. All examples achieved an antibacterial rate of over 99.5%, demonstrating excellent antibacterial properties.
[0072] Comparative Example 1 replaced the long-chain 8-glycidoxyoctyltrimethoxysilane with short-chain 3-glycidoxypropyltrimethoxysilane. The absence of the octyl flexible toughening arm resulted in a significant decrease in elongation at break. The weakened interfacial bonding led to a reduction in both heat distortion temperature and tensile strength. However, the antibacterial properties and self-healing efficiency remained relatively good due to the continued presence of dynamic bonds.
[0073] In Comparative Example 2, step S3 was omitted. The modified nanocellulose was not modified by a long-chain epoxy silane coupling agent, resulting in poor dispersibility in the PLA matrix and a significant decrease in both mechanical and heat resistance compared to the Example.
[0074] Comparative Example 3 omits steps S2 and S3. The modified nanocellulose, without SiO2 inorganic layer coating and coupling agent modification, has poor thermal stability and interfacial compatibility, and all properties are lower than those of Comparative Example 2.
[0075] Comparative Example 4 omits S2, S3, and 4,4'-dithiodiphenylbenzaldehyde. The cross-linked layer contains only imine bonds formed by glutaraldehyde and lacks disulfide bonds and a rigid benzene ring structure. It has poor thermal stability and its self-healing efficiency is reduced due to the contribution of a single imine bond.
[0076] Comparative Example 5 used completely unmodified nanocellulose, which severely aggregated in the PLA matrix, failing to exert any reinforcing or toughening effects. Furthermore, it lacked the PEI antibacterial component, resulting in a significant decrease in both antibacterial rate and self-healing performance.
[0077] Comparative Example 6 omitted the toughening agent, and the system lacked flexible toughening segments and guanidine antibacterial components, resulting in a significant reduction in both elongation at break and antibacterial rate.
[0078] Comparative Example 7 omitted modified nanocellulose, lacking inorganic reinforcing components and dynamic cross-linking network, resulting in a significant decrease in both heat resistance and self-healing properties.
[0079] The above-disclosed embodiments are merely a few specific examples of the present invention. However, the embodiments of the present invention are not limited thereto, and any variations that can be conceived by those skilled in the art should fall within the protection scope of the present invention.
Claims
1. A heat-resistant polylactic acid 3D printing filament, characterized in that, By weight, it includes the following parts of raw materials: Polylactic acid 50-80 parts; polybutylene succinate 10-30 parts; stereopolymer polylactic acid 5-20 parts; toughening agent 2-10 parts; modified nanocellulose 1-5 parts; antioxidant 0.1-1 part; lubricant 0.2-1.5 parts; The toughening agent is arginine polyester amide; The modified nanocellulose is a cross-linked nanocellulose with a surface coated with silica and modified with an epoxy silane coupling agent containing hydrophobic long chains. The cross-linked nanocellulose is formed by cross-linking polyethyleneimine with glutaraldehyde and 4,4'-dithiodibenzaldehyde.
2. The polylactic acid heat-resistant 3D printing filament as described in claim 1, characterized in that, The polylactic acid is L-polylactic acid with a melt index (190℃ / 2.16kg) of 5-15 g / 10min; The polybutylene succinate has a number-average molecular weight of 80,000 to 120,000 and a melting point of 110 to 120°C. The stereocomposite polylactic acid is composed of L-polylactic acid and D-polylactic acid in a mass ratio of 1:
1.
3. The polylactic acid heat-resistant 3D printing filament as described in claim 1, characterized in that, The toughening agent is prepared by: A1. Triethylamine and p-nitrophenol were added to acetone and the reaction was maintained at 0°C to obtain a cooling solution. 2,5-furandicarboxylic acid chloride was diluted in cold acetone and then added to the cooling solution. The mixture was stirred at 0°C for 2-3 hours and left overnight at room temperature. The precipitate was washed, recrystallized, and dried to obtain monomer 1. A2. L-arginine and 1,6-hexanediol were mixed, followed by the addition of toluene and p-toluenesulfonic acid monohydrate. The mixture was heated to 130°C and stirred under reflux for 24 hours. After cooling to room temperature, the toluene precipitated and was poured off. The product was then dissolved in isopropanol at 75°C under stirring, and then precipitated at 4°C to obtain monomer 2. A3. Add monomer 1 and monomer 2 to anhydrous DMSO, stir and dissolve at 120°C, add triethylamine, stop stirring, keep at 80°C overnight, add the mixed solution to pre-cooled ethyl acetate to precipitate, stir, wash, and dry to obtain toughening agent.
4. The polylactic acid heat-resistant 3D printing filament as described in claim 3, characterized in that, In step A1, the ratio of triethylamine, p-nitrophenol, and acetone in the coolant is 32.4g:43.1g:200mL; the ratio of 2,5-furandicarboxyl chloride, cold acetone, and coolant is 30g:100mL:200mL. In step A2, the ratio of L-arginine, 1,6-hexanediol, toluene, and p-toluenesulfonic acid monohydrate is 7g:2.4g:400mL:15.6g; In step A3, the ratio of monomer 1, monomer 2, anhydrous DMSO, and triethylamine is 0.73g:0.86g:3mL:5mL.
5. The polylactic acid heat-resistant 3D printing filament as described in claim 1, characterized in that, The method for preparing the modified nanocellulose is as follows: S1. Add polyethyleneimine to the nanocellulose dispersion, stir for 5-10 min, add glutaraldehyde aqueous solution and 4,4'-dithiodimethylbenzaldehyde solution, stir at 40-50℃ for 3-5 h, centrifuge, wash, and dry to obtain cross-linked nanocellulose; S2. Add cross-linked nanocellulose to an ethanol aqueous solution, then add tetraethyl orthosilicate, adjust the pH to 8, stir at 40-50℃ for 2-4 hours, centrifuge, wash, and dry to obtain SiO2@cross-linked nanocellulose; S3. Add SiO2@crosslinked nanocellulose to an ethanol aqueous solution, add 8-glycidoxyoctyltrimethoxysilane, stir and react at 50-60℃ for 2-4 hours, centrifuge, wash, and dry to obtain modified nanocellulose.
6. The polylactic acid heat-resistant 3D printing filament as described in claim 5, characterized in that, In step S1, the ratio of the aqueous dispersion of nanocellulose, polyethyleneimine, glutaraldehyde aqueous solution, and 4,4'-dithiodibenzaldehyde solution is 100 mL : 0.75–1.25 g : 0.6–1.2 mL : 2–6 mL; The ratio of nanocellulose to deionized water in the nanocellulose dispersion is 1g:100mL. The mass fraction of the glutaraldehyde aqueous solution is 25 wt%. The ratio of 4,4'-dithiodiphenylbenzaldehyde to anhydrous ethanol in the 4,4'-dithiodiphenylbenzaldehyde solution is 1 g: 15-25 mL.
7. The polylactic acid heat-resistant 3D printing filament as described in claim 5, characterized in that, In step S2, the ratio of the cross-linked nanocellulose, ethanol aqueous solution, and tetraethyl orthosilicate is 1g:50-80mL:2-5mL; the volume ratio of anhydrous ethanol to deionized water in the ethanol aqueous solution is 4:
1. In step S3, the ratio of SiO2@crosslinked nanocellulose, ethanol aqueous solution, and 8-glycidoxyoctyltrimethoxysilane is 1g:60-80mL:0.2-0.4g; the volume ratio of anhydrous ethanol to deionized water in the ethanol aqueous solution is 4:
1.
8. The polylactic acid heat-resistant 3D printing filament as described in claim 1, characterized in that, The antioxidant is vitamin E and / or rosemary extract; The lubricant is carnauba wax and / or bio-based stearate.
9. A method for preparing polylactic acid heat-resistant 3D printing filament, used to prepare the polylactic acid heat-resistant 3D printing filament according to any one of claims 1-8, characterized in that, Includes the following steps: (1) Weigh polylactic acid, polybutylene succinate, stereocomposite polylactic acid, toughening agent, modified nanocellulose, antioxidant and lubricant according to the weight parts, add them to a high-speed mixer to obtain a premix; (2) Add the premix to a twin-screw extruder and perform melt blending extrusion to obtain a melt blend; (3) The melt blend is cooled with water and pelletized to obtain granules; (4) The particles are dried and then added to a single screw extruder. After melting, extrusion, cooling, traction and winding, a 3D printing filament with a diameter of 1.75±0.05mm is obtained.
10. The method for preparing polylactic acid heat-resistant 3D printing filament as described in claim 9, characterized in that, In step (1), the specific parameters of the high-speed mixer are: mixing at a speed of 300-500 rpm for 5-15 minutes; In step (2), the specific parameters of the twin-screw extruder are as follows: the extruder temperature is set to 150-170℃ in zone 1, 170-190℃ in zone 2, 190-210℃ in zone 3, 200-220℃ in zone 4, the die head temperature is 210-225℃, and the screw speed is 200-300 rpm. In step (4), the specific parameters of the single screw extruder are: the temperature of the single screw extruder is 170-190℃ in zone 1, 190-210℃ in zone 2, 200-220℃ in zone 3, the die head temperature is 210-230℃, and the screw speed is 30-60 rpm. In step (4), the temperature of the cooling water tank is 20-40°C.